Peran Pendidikan Seni Tari dalam Membentuk Karakter dan Kreativitas Generasi Muda : Studi Kasus SMP Negeri 1 Wonogiri - Brilyant De Gusman; Galuh Fatma Hedianti (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The current education system is facing a crucial dilemma: the intensifying focus on cognitive achievement amidst the specific challenges faced by Generation Z. Junior high school students aged 12–15, who are digital natives, are at risk of reduced social interaction and mental health issues due to high screen time. Addressing this urgency, this study aims to describe the strategic role of dance arts education in shaping character and creativity, and to identify implementation solutions at SMP Negeri 1 Wonogiri. This descriptive qualitative study utilized 8 students active in dance as primary subjects, with data collected through observation, interviews, and documentation. The findings indicate that dance arts, through an embodied learning approach based on physical movement, is highly effective in cultivating character. Values such as discipline, which is transferred from the punctuality required in practice to general school life , collective responsibility , and self-confidence that overcomes social awkwardness, grew significantly. Furthermore, dance reinforces authentic cooperation and cultural appreciation. In terms of creativity, the activity encourages movement exploration, improvisation, and creative problem-solving. Psychologically, dance practice functions as a positive coping mechanism that effectively lowers adolescent stress levels. Although constraints exist, such as limited instructional time (80 minutes per week) , adaptive solutions like strengthening extracurricular activities and the peer tutoring system are being implemented. This research concludes that dance arts education is an essential and strategic medium for developing holistic competencies, including the 4Cs (Critical Thinking, Creativity, Collaboration, and Communication) and the Profil Pelajar Pancasila.